1 THERMAL SKIN HYPEREMIA AS A DIAGNOSTIC TOOL IN PERIPHERAL VASCULAR DISEASE. (1st January 2005) - Scremin, M.; Leach, C.; Kunkel, C.
Abstract : Peripheral vascular disease (PVD) is very prevalent, with 12% of the general population and 20% of older individuals being affected. The purpose of this study was to determine if non-invasive measurements of baseline flux (the product of blood flow velocity and blood volume) or thermal hyperemia (heat-induced flux increase) of the skin, in affected areas of patients with severe lower limb PVD could detect a perfusion deficit. In addition, the relative contributions of the co-morbid conditions diabetes mellitus (DM), congestive heart failure (CHF) smoking (SMO) and hypertension (HTN) to the flux data were evaluated. Cross-sectional study of 73 subjects with PVD involving analysis of skin perfusion images obtained with a laser Doppler Imager and the thermostatically controlled heating element of a TCO2M transcutaneous PO2/PCO2 monitor that elevated temperature of a circular skin area of 8 mm diameter to 44°C. The dissipation of the heat hyperemia with distance was quantified by fitting the values of flux beyond the border of the heating element (F) and their distance (D) to the first order rate equation: F = A * EXP(B*D)+ C. The parameter A represents the difference between flux at the border of the heating element and at the farthest (non-heated) distance away from it, B is the reciprocal of the space constant for flux decay and C is the asymptotic value of flux away from the heated area. These parameters were calculated by non-linear regression with a Newton-Gauss algorithm. Mean of parameter A (402.4) but not of parameters B (0.34) and C (109.9) of subjects with PVD were below the lower 95% confidence interval of laboratory normal values (A: 445.6-586.6; B: 0.29-0.40; C: 91.2-119.6). Stepwise multiple regression analysis indicated that HTN was the only co-morbid condition studied to significantly aggravate the decrease in parameter A. Image analysis of LDI data obtained from heated and non-heated areas of lower limb skin detected a decrease of heat hyperemia in subjects with PVD. The presence of the co-morbid condition HTN aggravated this deficit. Further exploration of the mechanism of this deficit and its potential prognostic value are warranted.